2012
DOI: 10.1603/me12037
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Fumigation for Controlling Bed Bugs

Abstract: We investigated the potential of carbon dioxide (CO2) fumigation as a method for controlling bed bugs, Cimex lectularius L. The effect of bed bug developmental stage, temperature, and CO2 concentration on the minimum time to kill 100% of bed bugs was determined. The minimum CO2 concentration lethal to all bed bug stages was approximately 30% with 24 h exposure time at 25 degrees C. The minimum fumigation time required to kill 100% of eggs using 100% CO2 at 20, 25, and 30 degrees C were 3, 7, and 8 h, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Biological control of urban insects is not considered to be feasible, but the ubiquitous association of the mutualistic bacterium Wolbachia with bed bugs and the inability of insects lacking this symbiont to reproduce may be exploited for biocontrol . Finally, modified‐atmosphere technologies that use CO 2 , liquid nitrogen, chlorine dioxide and ozone (Feston J et al ., unpublished data) show some promise for treatment of small bed bug‐infested items in sealed chambers. However, their use for whole‐room or dwelling treatments seems unpractical.…”
Section: Emerging Technologies For the Ipm Toolboxmentioning
confidence: 99%
“…Biological control of urban insects is not considered to be feasible, but the ubiquitous association of the mutualistic bacterium Wolbachia with bed bugs and the inability of insects lacking this symbiont to reproduce may be exploited for biocontrol . Finally, modified‐atmosphere technologies that use CO 2 , liquid nitrogen, chlorine dioxide and ozone (Feston J et al ., unpublished data) show some promise for treatment of small bed bug‐infested items in sealed chambers. However, their use for whole‐room or dwelling treatments seems unpractical.…”
Section: Emerging Technologies For the Ipm Toolboxmentioning
confidence: 99%
“…Rivnay (Rivnay, 1932) hypothesized that bed bugs search for hosts randomly and only in close proximity to hosts they detect and orient towards heat produced by the host. Marx (Marx, 1955) suggested that besides heat, CO 2 produced by hosts may play a role in attracting bed bugs, and this compound is usually incorporated in traps for monitoring bed bug infestations (Anderson et al, 2009;Wang et al, 2012). Although host odors are thought to play a role in the host-seeking process, chemicals collected from human emanations have not been shown to be attractive in behavioral assays (Harraca et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…39 Finally, locally producing small amounts of CO 2 could also be practical for fumigation, for instance of bed bugs. 40 Some cases however do require the use of very pure, 99% CO 2 . Enhanced Oil Recovery (EOR) for instance, injects CO 2 in near-depleted oil wells under supercritical conditions.…”
Section: Alternative Operating Conditionsmentioning
confidence: 99%